GAMBARAN KOMPETENSI MAHASISWA PRODI PIK ANGKATAN 2018 DALAM MEMBERIKAN PELAYANAN PENERIMAAN RAWAT INAP DI LABORATORIUM STIKES HUSADA BORNEO - Ermas Estiyana; Alis Lusiana Prayogi Putri (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2020)
A medical and health information recorder must have knowledges, skills, and behaviours which are the competencies of the profession. One of the medical recorder competencies is “registering for all the visits in health care facilities (registration for outpatient and inpatient)”. This reasearch aims to investigate the overview of students competencies of PIK Department batch 2018 in providing services for inpatient registration in STIKes Husada Borneo Laboratory. This research used descriptive qualitative method and was conducted on 56 students of STIKes Husada Borneo batch 2018. The sampling technique in this research was proporsiv sampling. Based on the results of the research, by using questionnaires and checklists, shows that the students’ knowledge of the competence and procedures for inpatient registration are; 3,5% good, 35,7% enough, and 60,7% less good, then the students’ attitude toward patients are good (98.2%) and less good (1.78%),and the students’ skills in inpatient registration are competent for 67.8% and not competent yet for 32.1%. So it can be concluded that the students’ competencies of PIK Department batch 2018 in providing services for inpatient registration in terms of knowledges, behaviours, and skills are not competent yet.